El análisis del flujo de caja y la toma de decisiones gerenciales del comercial Santa Inés, Iquitos 2021 - Rengifo Sanchez, Elsa Mireya (2021)
The objective of this study was to determine the relationship between cash flow analysis and managerial decision-making at Comercial Santa Inés, Iquitos 2021; Being a basic type research, descriptive and correlational level with a non-experimental design, which was composed of 24 workers, the survey technique and a questionnaire were used as a data collection instrument; Therefore, it was concluded that the analysis of the cash flow of Comercial Santa Inés is perceived as efficient (33%), because the company is feasible in the liquidity analysis while the profitability analysis only sometimes, likewise , it is evident that the income is almost always due to the good management of the client portfolio carried out by the entity. On the other hand, management decision-making is classified as regular (40%), because sometimes the problem is diagnosed in the company, likewise, rarely is priority given to the resolution of problems that greatly affect the company, however, decisions are almost always made that generate more investment in business activities. Finally, it was determined that the cash flow analysis of Comercial Santa Inés is considerably related to managerial decision-making, a situation that was contrasted by a correlation of 0.797.